ANALISIS PENGARUH IPM, PENGELUARAN PEMERINTAH DAERAH, DAN UMK TERHADAP POSISI PEREKONOMIAN DAERAH (Studi Kota dan Kabupaten di Provinsi Jawa Timur) - Ida Farida A Bernadina (Universitas Negeri Malang, 2014)
Topic of this research is analysis of HDI’s impact, Local Government Expenditures and minimum wage of city/regency toward regional economic position. Moreover, this research determine several variables such as: (1) the effect of HDI toward the regional economy position, (2) the influence of local government expenditure toward the regional economy position, (3) the effect of City / Regional Minimum Wage toward position the regional economy position, and (4) the effect of HDI, government expenditure and City / Regency Minimum Wage toward the region's economy position. This research using descriptive statistical analysis tools that consists of Klassen’s Regional Typology Model, LQ and Multinomial logit analysis model. By klassen’s typology, it is known each positions of region in East Java Province, where most of area are include to the fourth quadrant with most of basis sector is an agriculture. Keywords: HDI, Local Government Expenditure, Regional Minimum Wage, Regional economy position, Klassen’s Typologi